(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The study analysed various scientific approaches to the problem of forming a customer-oriented strategy for enterprise development. Thus, the study has identified several key approaches that contribute to the creation of an effective customer orientation strategy. The stages of formation of a customer-oriented development strategy for operators in the organic market. The main components of the customer-oriented development strategy of operators in the organic market are identified in terms of key aspects: development and innovation in the product range; introduction of effective marketing communication; improvement of service quality; development of partnerships.